Solid State Photoluminescence Studies of [Eulnh2(No3)3](H2o)X Macrocyclic Complexes with Schiff Base Ligands - Venegas-Yazigi, D; Venegas-Yazigi, D; Aravena-Ponce, D; Aravena-Ponce, D (Elsevier B.V., 2018)
Three EuIII macrocyclic complexes [EuLnH2(NO3)3](H2O)x based on the ligands derived from 2-hydroxy-5-methyl-1,3-benzenedicarbaldehyde and three different amines: o-phenylenediamine, Eu-OPDA; ethylenediamine, Eu-EDA; and 1,3-diaminopropane, Eu-DAP have been synthesized via a metal template reaction. Eu-EDA and Eu-DAP showed metal based emission; for the Eu-OPDA complex these luminescent properties were not observed. From the photoluminescence emission measurements from ~13 to 300 K, the R/O = I (5D0 → 7F2)/I (5D0 → 7F1) ratio, together with two intensity parameters (Ω2 and Ω4), radiative lifetimes (τR) and branching ratios (β0 J′) were calculated based on the Judd-Ofelt theory, for Eu-EDA and Eu-DAP. While the behavior of these parameters for the Eu-DAP complex is temperature dependent, these remain constant for Eu-EDA. The temperature dependence observed for the Eu-DAP complex indicates that for temperatures below 120 K, the local symmetry of the EuIII center is modified, as compared to the environment of the same metal center at room temperature. © 2018 Elsevier B.V.